Chinese University Students’ Intercultural Competence: Reconceptualization and Assessment - Zhang, Xiaotian; Zhou, Mingming (Journal of International Students, 2023)
Intercultural competence (IC) is considered as an essential soft skill for successful functioning in the globalized society in the 21st century. However, there is still a lack of culturally appropriate framework and instrument to understand and assess Chinese university students’ IC development. The purpose of this study was to design a valid and reliable scale for assessing Chinese students’ IC. Based on the AAA (Approach-Analyze-Act)-Chinese framework, a 30-item Intercultural Competence Scale-Chinese Version (ICS-CHN) was developed and validated with confirmatory factor analysis. Subsequent multigroup confirmatory factor analysis model further proved the measurement invariance of ICS-CHN in different gender groups. Together with its adequate reliability, convergent and discriminant validity, it is reasonable to conclude that ICS-CHN is a reliable and valid scale, corroborating that IC is a combination of affective/attitudinal, cognitive and behavioral skills and characteristics applied in intercultural encounters.